'If I am on ART, my new-born baby should be put on treatment immediately': Exploring the acceptability, and appropriateness of Cepheid Xpert HIV-1 Qual assay for early infant diagnosis of HIV in Malawi - Maggie Nyirenda-Nyang'wa; Moses Kelly Kumwenda; Shona Horter; Mina C. Hosseinipour; Maganizo Chagomerana; Neil Kennedy; Derek Fairley; Kevin Mortimer; Victor Mwapasa; Chisomo Msefula; Nigel Klein; Dagmar Alber; et al. (Public Library of Science (PLoS), 2023)
Early infant diagnosis of HIV (EID-HIV) is key to reducing paediatric HIV mortality. Traditional approaches for diagnosing HIV in exposed infants are usually unable to optimally contribute to EID. Point-of-care testing such as Cepheid Xpert HIV-1 Qual assay-1 (XPertHIV) are available and could improve EID-HIV in resource constrained and high HIV burden contexts. We investigated the acceptability and perceived appropriateness of XpertHIV for EID-HIV in Mulanje Hospital, Malawi. Qualitative cross-sectional study using semi-structured interviews (SSI) among caregivers and health care workers at Mulanje District Hospital. The qualitative study was nested within a larger diagnostic study that evaluated the performance of XpertHIV using whole-blood-sample in a resource limited and high burden setting. A total of 65 SSIs were conducted among caregivers (n = 60) and health care providers (n = 5). Data were coded using deductive and inductive approaches while thematic approach was used to analyse data. Point-of-care XPertHIV was perceived to be acceptable among caregivers and health care providers. Caregivers' motivations for accepting XPertHIV HIV-testing for their infants included perceived risk of HIV emanating from child's exposure and validation of caregiver's own HIV sero-status. Although concerns about pain of testing and blood sample volumes taken from an infant remained amplified, overall, both caregivers and health care providers felt XpertHIV was appropriate because of its quick result turn-around-time which decreased anxiety and stress, the prospect of early treatment initiation and reduction in hospital visits and related costs. Implementation of XpertHIV has a great potential to improve EID-HIV in Malawi because of its quick turn-around-time and associated benefits including overcoming access-related barriers. Scaled implementation of this diagnostic technology require a robust community engagement strategy for managing caregivers and community myths and misconceptions towards the amount of blood sample collected from infants.